Clinical characteristics, comorbidities and mortality in critically ill mechanically ventilated patients with Covid-19: a retrospective observational study - Adisa Šabanović Adilović; Nermina Rizvanović; Mirza Kovačević; Harun Adilović (Medicinski glasnik, 2021)
Aim: To analyse demographic data, clinical symptoms and signs, laboratory data and comorbidities in patients with COVID-19 pneumonia admitted to the intensive care unit (ICU), mechanically ventilated with fatal outcome. Methods: Medical records of 92 patients were retrospectively analysed. Demographic data, clinical symptoms and comorbidities were collected on the day of hospital admission. Clinical signs and laboratory data were collected on the day of hospital admission (T1), on the day of starting non-invasive ventilation (T2), and on the day of starting invasive ventilation (T3). Results: Average age of the patients was 60.05 years. Patients over 50 years of age, 71 (77.1%) (p=0.000), and males, 62 (67.4%; p=0.001) were predominant. The most common patient symptoms were exhaustion, myalgia, dyspnoea and cough. Hyperthermia was recorded on the day of hospital admission. Tachycardia, hyperglycaemia, hypoxemia were recorded at all observed study times. The most common comorbidity was hypertension arterialis with a very strong correlation with fatal outcome, followed by diabetes mellitus and chronic heart disease that were moderately correlated with fatal outcome. Conclusion: The treatment of COVID-19 patients in ICU with mechanical ventilation has a high failure rate. Demographic data, clinical symptoms and signs as well as accompanying comorbidities can be a significant component in making decisions about diagnostic-therapeutic procedures.
Keywords: comorbidity; fatal outcome; intensive care unit; invasive ventilation